Peran Kelompok Sadar Wisata (Pokdarwis) Wana Abadi Dalam Pengelolaan Wisata Growgoland Water Fun Desa Ngunut Kecamatan Dander Kabupaten Bojonegoro - Ananta Prathama; Putri Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Tourism is an important sector in the economy that can make a significant contribution to regional income and the welfare of the local community. In Indonesia, Pokdarwis also plays an important role in the development and management of local tourist destinations. One example is Pokdarwis Wana Abadi who manages Growgoland Water Fun, a water tourism destination located in Ngunut Village, Dander District, Bojonegoro Regency. The purpose of the research is to find out what the role of Pokdarwis Wana Abadi in the management of Growgoland Water Fun tourism in Ngunut Village, Dander District, Bojonegoro Regency. The research method used is qualitative descriptive with data collection methods through interviews, observations, and documentation. Data analysis in this study is through data collection, data condensation, data presentation and conclusion drawn. The results of the study show the role of Pokdarwis Wana Abadi in the management of Growgoland Water Fun tourism. These roles are in facilitating, educating, representational, and technical. Pokdarwis Wana Abadi plays a role in facilitating by encouraging the surrounding community to participate in managing tourism, becoming a mediator when there are obstacles in management such as when there are problems regarding the location of stalls that are too close to the flow of water sources, and providing facilities. In educating, Pokdarwis Wana Abadi provides awareness to the community to reduce the use of water sources for daily activities, and receives training to manage tourism. In representation, Pokdarwis seeks to obtain a source of funding, one of which is by sending a proposal to Exxon Mobil Cepu Limited, and using the media well for promotional activities. Technically, Pokdarwis Wana Abadi uses computers to compile reports and proposals, then manage finances according to tourism needs.